Meta-analysis of microsatellite instability in relation to clinicopathological characteristics and overall survival in gastric cancer. Issue 3 (1st November 2017) - Polom, K; Marano, L; Marrelli, D; De Luca, R; Roviello, G; Savelli, V; Tan, P; Roviello, F
Abstract: Background: Several associations between microsatellite instability (MSI) and other clinicopathological factors have been reported in gastric cancer, but the results have been ambiguous. This systematic review and meta-analysis investigated the relationship between MSI and overall survival and clinicopathological characteristics of patients with gastric cancer. Methods: A systematic literature search of the PubMed, Cochrane and Ovid databases until 31 January 2016 was performed in accordance with the PRISMA statement. The articles were screened independently according to PICO (population, intervention, comparator, outcome) eligibility criteria. All eligible articles were evaluated independently by two reviewers for risk of bias according to the Quality In Prognosis Study tool. Results: Overall, 48 studies with a total of 18 612 patients were included. MSI was found in 9·2 per cent of patients (1718 of 18 612), and was associated with female sex (odds ratio (OR) 1·57, 95 per cent c.i. 1·31 to 1·89; P < 0·001), older age (OR 1·58, 2·20 to 1·13; P < 0·001), intestinal Laurén histological type (OR 2·23, 1·94 to 2·57; P < 0·001), mid/lower gastric location (OR 0·38, 0·32 to 0·44; P < 0·001), lack of lymph node metastases (OR 0·70, 0·57 to 0·86, P < 0·001) and TNM stage I–II (OR 1·77, 1·47 to 2·13; P < 0·001). The pooled hazard ratio for overall survival of patients with MSI versus those with non-MSI gastric cancer from 21 studies was 0·69 (95 per cent c.i. 0·56 to 0·86; P < 0·001). Conclusion: MSI in gastric cancer was associated with good overall survival, reflected in several favourable clinicopathological tumour characteristics. Abstract : Microsatellite instabililty subgroup does better